EPIDEMIOLOGICAL MONITORING OF POLIOMYELITIS IN THE CENTRAL AFRICAN REPUBLIC FROM 2004 TO 2017 AND IMPLEMENTATION OF POLIOVIRUS ENVIRONMENTAL SURVEILLANCE IN BANGUI IN 2017 - J. Doté (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
.